Two Channel Thermally Tunable Band-Stop Filter for Wavelength Selective Switching Applications by Using 1D Ternary Superconductor Photonic Crystal - Upadhyay M.; Awasthi S.K.; Shiveshwari L.; Shukla S.N.; Ojha S.P. (My University, 2025)
By studying temperature-dependent dispersion characteristics and group velocity of 1D ternary photonic crystal (TPC) composed of dielectric-superconductor-dielectric materials, a thermally tunable band-stop filter which is capable of stopping unique wavelength channels without causing any interference amongst equally spaced wavelength channels of full width at half maximum of 1 nm each as per the requirement of wavelength division multiplexing standards adopted by the International Telecommunication Union specifying channel spacing in terms of frequency (wavelength) is suggested. The proposed structure can efficiently work as a two-channel wavelength selective switch for wavelength division multiplexing (WDM)-based all-optical networks. This study also gives theoretical insight to design some new kind of optical memories and tunable buffers which holds data temporary and have potential applications in modern communication systems. © 2015, Springer Science+Business Media New York.